Administrative and Topographic Map of Kelurahan to Support Land Efficiency and Flood Mitigation - Refrizon,; Farid, Mochammad; Ekawita, Riska; Fauzi, Hera Wahyu; Anggria, Della Cici; Prasetyo, Rendi Dwi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The community service activity by the University of Bengkulu Geophysics and Physics Team aimed to assist the community of Kandang Limun, Bengkulu City, by developing maps that display area boundaries and topographical elevations. The maps were intended to serve as easily accessible sources of information for the local community and to aid in planning and development efforts. Method: The methodology involved conducting a preliminary survey, collecting data, preparing software tools, and creating both boundary and topographic maps. A questionnaire was distributed to assess community satisfaction with the project. Practical Applications: The maps provide valuable information for local government and residents, serving as a resource for defining area boundaries and understanding topographical features. These maps are particularly useful for urban planning, land use, and community development initiatives. Conclusion: The creation and public display of administrative and topographical maps in the Kelurahan office have improved access to essential geographical information. This initiative supports better community planning and contributes to the informed development of the area, benefiting both the local government and residents.